2013
DOI: 10.33687/phytopath.002.01.0076
|View full text |Cite
|
Sign up to set email alerts
|

Mass Production of the Beneficial Nematode Steinernema carpocapsae Utilizing a Fed-Batch Culturing Process

Abstract: The present study deals with the batch and fed-batch mass production of Steinernema carpocapsae. S. carpocapsae is an entomoparasitic nematode that is used as a biological control agent of soil-borne crop insect pests. The ability and efficiency of fed-batch culture process was successful through the utilization of the nematode’s bacterial symbiont Xenorhabdus nematophila. Results from the fed-batch process were compared to those obtain from the standard batch process. The fed-batch process successively improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The time and concentration of the nematode inoculum along with nematode recovery greatly affect final yield [62,63]. Mass production strategies involving S. carpocapsae, H. bacteriophora and their bacterial symbionts have been developed by many while studying characteristics of both symbiotic partners in liquid culture [37,38,64,65]. Inman III and Holmes have described the role of trehalose, a non-reducing sugar found in abundance within insect hemolymph that seems to aid in maintainence of Phase I variant of P. luminescens over extended periods of time [66].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time and concentration of the nematode inoculum along with nematode recovery greatly affect final yield [62,63]. Mass production strategies involving S. carpocapsae, H. bacteriophora and their bacterial symbionts have been developed by many while studying characteristics of both symbiotic partners in liquid culture [37,38,64,65]. Inman III and Holmes have described the role of trehalose, a non-reducing sugar found in abundance within insect hemolymph that seems to aid in maintainence of Phase I variant of P. luminescens over extended periods of time [66].…”
Section: Resultsmentioning
confidence: 99%
“…Maximum average yields of EPNs reported were in shake flask batch cultures were 300,000 and 320,000 IJs per ml for H. bacteriophora and S. carpocapsae, respectively [36]. Furthermore, in a recent study, fermentation modes (batch and fed-batch) for mass producing S. carpocapsae were compared and found that fed-batch modes produced an 8.8-fold higher IJ yield than batch modes [37].…”
Section: Nematode Biology and Life Cyclementioning
confidence: 99%
“…From a mass production perspective, fold is not always the preferred measurement of success. Another approach to commercialization might be to shorten the 'recovery period' of IJs [19], [20]. The exit from the developmentally arrested third juvenile stage (IJ3) is called "recovery."…”
Section: F Nematode Yieldmentioning
confidence: 99%
“…After 2 weeks the hatched juveniles were collected and incubated overnight in a solution containing 100 μg/ml each of ampicillin and streptomycin (w/v) on a rocker (Standard Analog Rocker, VWR, USA) at 22˚C. The nematode suspension was fur-ther treated with benzethonium chloride (0.125%) by continuous shaking for 20 min, washed 8 times by centrifugation at 4000 rpm for 10 min, and re-suspended in sterile distilled water [14]. Collected J2s (300 J2s/100μL) were suspended in a solution of PKH26 (4 × 10 −6 M, as per manufacturer's protocol, Sigma Aldrich, USA), incubated for 10 mins at 22˚C with intermittent shaking (3 times for 15 s), and washed 5 times in sterile distilled water.…”
Section: Globodera Pallida Culture and Preparation Of Nematode Inoculummentioning
confidence: 99%